DISEASE CONTROLLING IN FARM KECAMATAN ALIAN KABUPATEN KEBUMEN (Universitas Wijayakusuma Purwokerto, 2024)
Livestock health is a very important aspect in the success of livestock cultivation. Biosecurity and livestock health management are two things that cannot be separated in order to achieve the goal of increasing livestock production and livestock health status. The ultimate goal of every livestock business is to achieve profits. Maximum profits will only be achieved if all livestock are in healthy condition, because livestock are able to produce optimally if they are in a healthy condition. This service activity was carried out in Alian District, Kebumen Regency. The method used is socialization and assistance to farmer breeders. The results achieved in the service are increased farmer knowledge regarding biosecurity, diseases that often appear in livestock and how to anticipate them.